Students’ utilization of their indigenous languages as resources that bolster dialogical participation during their learning - Zulu, Ntokozo; Gumede, Mzuyabonga (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
The exclusive use of English as a Medium of Instruction (MoI) in South African higher education sometimes creates barriers to students’ access to knowledge, knowledge sharing and knowledge construction; more especially to students who use English as a second language. The objective of this conceptual paper is to argue that the use of the indigenous languages alongside English, has a potential to encourage students to dialogically participate in their learning using existing knowledge as their frame of reference. The body of literature that the authors have reviewed communicates the historical facts that the indigenous languages have always been put on the margins in the South African learning spaces. Therefore, the author’s line of argument tries to suggest that indigenous languages can be utilized as resources for learning. Dialogical participation enables students to express their views effortlessly and meaningfully through applying their critical thinking capabilities. The students who can reflectively and critically think in their indigenous languages have a potential to develop skills that can enable them to make informed and decisive decisions. In addition, dialogical participation cognitively develops students to be creative problem-solvers in their social worlds and ultimately in their worlds of work. The utilization of indigenous languages for learning decolonizes the unjust imposition of colonial languages as the only ones that can be used for epistemological access and knowledge creation. Thus, the valuing of the indigenous languages and knowledge in a dialogue is an act of ubuntu, which is part of collectivity and equality. The researchers, therefore, premise their argument on student-centered learning in that the students can be academically developed to cooperatively shape and own their learning in the medium of dialogic engagements under the auspices of their indigenous languages and English as a lingua franca.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 3, Volume 8, 2024 Special Issue
Keywords: Critical thinking; Dialogical engagements; Decolonization; Indigenous languages; Student-centered learning; Ubuntu; Student-centered learning; Academic achievement; Education, Higher -- South Africa; Indigenous peoples -- Languages; Critical thinking -- Study and teaching (Higher)